The mediating role of reflective moral attentiveness between organizational identification, perceived insider status and unethical pro-organizational behaviors - Abdul Rauf Qureshi; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Unethical pro-organizational behaviors (UPB) are generally defined as behaviors that are unethical but at the same time intended to help the organizations warrant renewed attention to address its long-termimplications.Drawing from social exchange theory (SET), the goals of this research are to investigateeffects of perceived insider status (PIS) and organizational identification (OID) on UPB through reflective moral attentiveness (RMA). Data was collected from 300 managerial employees from services sector of Punjab, Pakistanand subjected to hierarchical regression analysis and structural equation modeling with the help of SPSS 23. The results confirm significant positive effects of perceived insider status and organizational identification on UPB and mediation effect of reflective moral attentiveness. The study is first to incorporate RMA as mediator in associations of PIS and OID with UPB.The managers should make their employees conscious of short-termbenefits and long-termharmful consequences of UPB. Theyshould expand the intellectual abilities of their employees enabling them to think before performing the UPB. Additionally the organizations can place morally attentive employees at key positions to promote the culture of morality. The organizational executives can be role models for observing the moralprinciplesand shouldrecruit the morally attentive managers / employeesand maydirectfrequent analytical and integrity programs to endure an environment of morality. Turning the managers and employees sensitive to moral matters, the organizations can eliminate UPB.
Keywords: 330; perceived insider status; organizational identification; unethical pro-organizational behaviors; reflective moral attentiveness; social exchange theory; social cognitive theory